RANTAI NILAI BUNGA POTONG Heliconia caribaea DESA KERTA, KECAMATAN PAYANGAN, KABUPATEN GIANYAR, PROVINSI BALI - Novita, K. Ayu; Satriawan, I Ketut; Anom Yuarini, Dewa Ayu (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2016)
This study aims (1) to know the general picture of business of cutting flower Heliconia caribaea, (2) to determine the pattern of value chain of cutting flowers Heliconia caribeae that sold in Kerta Village, District Payangan, Gianyar and (3) calculate the value added at each stage of pattern the value chain of cutting flower Heliconia caribeae. This research involved of 26 farmers randomly selected, 4 traders, and 10 retailers. Data were analyzed descriptively on the pattern of value chain and marketing margin of cutting flower Heliconia caribeae. Cultivation cutting flower Heliconia caribeae in the Kerta village began in 2002, and currently has five farmer groups with more than 15 kinds of varieties. Harvesting is done every two weeks and once the harvest could produce 300 cutting flowers. Pattern of value chain Heliconia caribeae in Kerta village there are two, namely first; farmers to traders to retailers to consumers; the second, from the farmer to the consumer. The added value to the traders have of Rp. 1.000,-/stalk, and retailers of Rp.2.000,-/stalk. Keywords : cutting flowers, value chain, marketing margin
Keywords: 83